Statutory Recognition of Native Customary Rights under the Sarawak Land Code 1958: Starting at the Right Place - Bulan, Ramy (Journal of Malaysian and Comparative Law, 2007)
This paper traces the historical development of the law on native customary rights through the Land Code and its predecessors and the creation of native customary lands ("NCL"). It discusses the use of certain terminologies to describe native rights, which are alien to native concepts of land ownership, and the nebulous recognition that has ensued. It analyses the amendments that have since been made to the Code, which have redefined the character as well as extinguishment of NCR. Furthermore, it highlights the aspects of the legislation that undermines native rights or are inconsistent with native laws and customs and the provisions of the Federal Constitution. This writer argues that the Land Code should not used as the sole and ultimate bias for interpretation and determination of NCR, because native title is based on occupation, in accordance with the native communities’ traditional laws and customs.